Analyzing Performance and Agricultural Impacts of the Mahakali Irrigation System, Phase-I - Negi, Crimsan S; Oli, Bijaya Kumar; Joshi, Bashu Dev; Pant, Ganesh; Joshi, Hemant Prasad; Kunwar, Himal (Journal of Engineering Technology and Planning, 2025)
Irrigation infrastructure plays a pivotal role in ensuring food security and sustaining livelihoods. The Mahakali Irrigation System, Phase-I (MIS-I), a national pride project of Nepal, was developed to irrigate over 3,400 hectares in Kanchanpur district. This study evaluates the structural performance, water management efficiency, agricultural impacts, and governance mechanisms of MIS-I to determine its effectiveness and sustainability. A mixed-methods approach was adopted, combining field inspections, structured household survey (No. of Households, n=108) across upstream, midstream, and downstream distributaries. Performance indicators were drawn from four dimensions: structural integrity, water availability and management, institutional governance. The results indicate that although MIS-I has enhanced agricultural productivity, with 65% of farmers reporting moderate yield improvements and 66% observing crop diversification, substantial challenges persist. Around 40% of farmers indicated facing water scarcity during the critical crop sowing months of May and June, while 24% cited poor maintenance causing blockages, sedimentation, and vegetation growth. Tail-end farmers (n=17) experience greater inequities in water distribution compared to head-reach users. Awareness of Water User Associations (WUAs) was found moderate (n=56), with mixed perceptions of their performances (n=40 out of 108 rating “Good”). The study concludes that MIS-I contributes significantly to food security and livelihoods but requires targeted interventions, including systematic maintenance, equitable allocation, WUA capacity-building, and technological upgrades. Strengthening these aspects is essential for enhancing resilience, optimizing water use, and advancing sustainable agricultural development.